Depth-social interaction between ethnic in the local culture of Minahasa - Winoto, Darmawan Edi; Dasfordate, Aksilas; Pelealu, Aldegonda Evangeline; Burdam, Yohanes; Ramaino, Almen Sulpedi; Dasfordate, Gamar (Program Pascasarjana Universitas Negeri Yogyakarta, 2023)
Humans benefit greatly from culture, especially social interaction. Humans' social interaction development will influence connection patterns with the environment. The Minahasa ethnic groups' unity of life grew from the small setting, namely the nuclear and extended family, and subsequently into a village. The social structure based on this relationship type is more inherited. This article explains the Minahasa culture, specifically interaction patterns. The method used is qualitative. Data collection used detailed observation, interviews, and studies bibliography. They use content analysis on reports and examination results from various events in the research area, especially regarding cooperation. The data collected were analyzed qualitatively. Research results show that relationships between family members by genetics or ethnicity are generally close ties. Kinship based on marriage is influential in social life. The market has cooperativeness, friendship, kinship, and patron-client service. In collaboration, the Minahasa and Sanger Talaud ethics are better than the Gorontalo ethics. Ethnic Minahasa and Sangir Talaud have developed many ideas to form harmonious activities between fellow citizens. Cooperation between people from different cultures in Minahasa is quite good in religion. The relationship between religious communities in Minahasa is the mutual respect in their respective worship.